2006
DOI: 10.1177/0739986305285823
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Media Literacy

Abstract: Transnational Latina teens use media as key cultural resources to manage their passage to womanhood while building identities as U.S. citizens. This article examines the challenges of media literacy within the transnational context of working-class Latinas. It presents findings of an action-research project with 12 Latina teens, which was grounded on Freire’s (1999) pedagogy and Willis’s (1981) insights about class culture. The study found that the hybridity of the teens’ media practices came not only from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…Importantly, some of these studies examine such knowledge and critical awareness among members of nondominant groups themselves. Doing so extends research conclusions regarding media consumers' self-perceptions, in ways that challenge and defy the narrow mainstream depictions (Vargas, 2006;Yosso, 2002). There is some evidence that media literacy education can promote an understanding of the systemic and structural conditions that shape racial conditions in society (Dunlop, 2007).…”
Section: Qualitative Approachesmentioning
confidence: 78%
See 2 more Smart Citations
“…Importantly, some of these studies examine such knowledge and critical awareness among members of nondominant groups themselves. Doing so extends research conclusions regarding media consumers' self-perceptions, in ways that challenge and defy the narrow mainstream depictions (Vargas, 2006;Yosso, 2002). There is some evidence that media literacy education can promote an understanding of the systemic and structural conditions that shape racial conditions in society (Dunlop, 2007).…”
Section: Qualitative Approachesmentioning
confidence: 78%
“…Students who had participated in the lessons were able to articulate the notion that popular media helped to form their impressions of the Middle East, and they used their own research about the region to identify stereotypes and inaccuracies within visual images supplied by the researchers and within a 13minute clip from the film, Aladdin. Vargas (2006) worked with a group of transnational Latina teenagersforeign-born or first-generation female U.S. adolescents-in a program focused on resistance of the stereotypical, often pejorative, media portrayals of Hispanic and Latina individuals. Using an ethnographic, in-depth interview method, Vargas observed that, toward the completion of the program, the participating teenagers showed recognition of the underrepresentation and stereotypical depictions of Latinos/as in media and examined the distance between their own perceptions of self and the mainstream depictions they critiqued.…”
Section: Qualitative Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous research findings across youth arts organizations that work with marginalized youth to make plays (Wiley & Feiner, 2001;Worthman, 2002;Halverson, 2007Halverson, , 2008a, digital stories (Hull & Katz, 2006), and films (Fleetwood, 2005) of the stories of their lives. While communities, and particularly the marginalized communities to which these youth belong, have a prominent role in both the process (Halverson, 2007) and the products (Bing-Canar & Zerkel, 1998;Mayer, 2000;Fleetwood, 2005;Vargas, 2006;Halverson, in press) of digital art-making, the unit for change is the identity development of individual members of these marginalized communities.…”
Section: Discussionmentioning
confidence: 98%
“…Due to its broad scope, however, the report lacks specific information about the work youth do, how they learn to do it, and what their products represent. A small group of scholars have detailed the work youth do across a variety of youth media organizations including film (Bing-Canar & Zerkel, 1998;Mayer, 2000;Fleetwood, 2005;Vargas, 2006), digital story (Hull & Nelson, 2005;Hull & Katz, 2006), spoken word digital poetry (Jocson, 2005) and radio (Soep, 2006). These studies are primarily participant observation studies, where program designers report on the work they did with a group of youth, how the process went and the products that resulted.…”
Section: Identity Development In Youth Media Arts Organizationsmentioning
confidence: 97%